Penerapan Teknik Mind Mapping Berbantuan Media Visual Minim Teks untuk Meningkatkan Motivasi Belajar Siswa Sekolah Dasar - Firnanda Pramestya; Hesti Nur Anggraini; Laela Sitarusmi Danadyaksa; Syailin Nichla Choirin Attalina (Jurnal Ilmiah Literasi Indonesia, 2026)
Learning motivation is one of the key factors influencing the success of the learning process in elementary schools. Low learning motivation often results in limited student participation, reduced attention during lessons, and lower achievement of learning objectives. This study aimed to improve students' learning motivation through the implementation of mind mapping techniques assisted by low-text visual media. The research employed Classroom Action Research (CAR) conducted in two cycles, consisting of planning, action, observation, and reflection. The participants were elementary school students who demonstrated low learning motivation. Data were collected through observation, learning motivation questionnaires, interviews, and documentation. The data were analyzed using descriptive quantitative and qualitative techniques by comparing the results from the pre-cycle, Cycle I, and Cycle II. The findings revealed that the implementation of mind mapping assisted by low-text visual media successfully improved students' learning motivation. The improvement was reflected in students' attention, participation, enthusiasm, collaboration, and engagement during the learning process. The use of simple but attractive visual media facilitated students' understanding of the learning materials, while mind mapping encouraged them to think actively, creatively, and systematically. Therefore, mind mapping techniques assisted by low-text visual media can serve as an effective learning alternative to enhance elementary school students' learning motivation.